Economic Valuation of Mangrove Ecosystem in Rempang Island, Batam City, Kepulauan Riau Province - Alamanda, Ladies Nikita; Ismail, Khodijah; Wahyudin, Wahyudin; Suryanti, Ani; Habibah, Sayyidah Nur (Jurnal Perikanan dan Kelautan, 2024)
This study aimed to determine and analyze the economic value of the mangrove ecosystem in Rempang Island, Batam City, Kepulauan Riau Province. The survey method used a quantitative approach to analyze the economic valuation with the calculation of Total Economic Value (TEV), which consists of the calculation of use value: direct use value, indirect use value, option value, and non-use value: existence value and bequest value. There were 44 respondents determined by the Slovin method. The results showed that the total economic valuation of mangrove ecosystems on Rempang Island with an area of 2,813.18 ha which is IDR 75,082,590,695/ year, consisting of a total use value which is IDR 74,739,030,695/year and total non-use value which is IDR 343,560,000/year. The use value is obtained from direct use value which is IDR 2,059,200,000/year from fish, shrimp, and crab utilization activities, indirect use value which is IDR 72,004,878,483/year from breakwaters and abrasion, preventing seawater intrusion, nursery ground, feeding ground, spawning ground, and an optional value which is IDR 674,952,212/year from the value of biodiversity. Then, the total non-use value is obtained from the willingness to pay IDR 137,640,000/year and bequest value IDR 205,920,000/year. These findings indicate that the current ecological condition of the Rempang Island mangrove ecosystem has provided excellent economic value, so efforts are needed to maintain this condition with sustainable management.